Recovering probabilistic information from options prices and the underlying - Bruce Mizrach (Rutgers University, Department of Economics, 2008)
This paper examines a variety of methods for extracting implied probability distributions from option prices and the underlying. The paper first explores non-parametric procedures for reconstructing densities directly from options market data. I then consider local volatility functions, both through implied volatility trees and volatility interpolation. I then turn to alternative specifications of the stochastic process for the underlying. I estimate a mixture of log normals model, apply it to exchange rate data, and illustrate how to conduct forecast comparisons. I finally turn to the estimation of jump risk by extracting bipower variation.
Keywords: G12; G14; F31; 330; Options; implied probability densities; volatility smile; jump risk; bipower variation